الاستشهاد بالشعر في الفقه الحنفي، فتح القدير شرح الهداية لابن الهمام أنموذجًا: Poetic Citation in Hanafi Jurisprudence, Fathul Qadeer by Ibn al Humam as a sample - Dr Hafiz Muhammad Altaf (Al Manhal Research Journal, 2024)
The term Al Fiqh (jurisprudence) was derived from Qur’an and Hadith; therefore, we see that books of jurisprudence, especially books about Fundamentals of Al-Fiqh, are full of linguistic discussions. In the structural division, Usul al-Fiqh (Fundamentals of Al-Fiqh) tends to focus on purely linguistic discussions from which the issues of jurisprudence were taken. Therefore, it is required for the jurist to have special knowledge of the Arabic language and its sciences so that he can extract the issues in the manner in which the word was mentioned in the Arabs’ custom. This article focuses on the linguistic aspect and the linguistic structure of jurisprudential issues, and discusses the citation of poetry in books of jurisprudence, and Fatah al-Qadir’s explanation of al-Hidayah in Hanafi jurisprudence is presented as an example in this regard. The article examines Ibn al-Humam’s method of citation of poetry and it's explanation in his book, and thus the importance of the Arabic language in addressing jurisprudential issues will be demonstrated, and that whoever embarks on writing jurisprudence must equip himself with the sciences of language before it, so that his understanding is sound and his efforts are correct. The study’s method is analytical and descriptive, as the evidence is mentioned under his method with a brief description of the author’s method in that. Finally, some results are mentioned, along with some recommendations and suggestions for researchers and students in this regard.